Analysis of age-related CpGs for forensic purpose in Chinese Han population. (December 2015) - Huang, Y.; Yan, J.; Zhuk, H.; Fu, X.; Hou, Y.
Abstract: Age-related CpGs (AR-CpGs) have been proved to be potential markers for forensic age prediction. However, DNA methylation (DNAm) patterns in particular AR-CpGs may be tissue specific. Meanwhile, variant methylation quantitative platforms might result in discrepant candidate markers. Recent researches carried out either by pyrosequencing or by microarray platforms were based on Caucasian samples. In this study, we aimed to screen out the AR-CpGs as potential forensic age prediction biomarkers in Chinese Han population by pyrosequencing approach. We referred the previous age-related DNAm studies with different methods or tissue specimens, candidate markers located on 6 gene fragments were selected for DNA methylation analysis. The blood samples both from younger donors aged from 10 to 25 years and from senior donors aged from 55 to 65 years were employed to screen the candidate markers with remarkable difference in methylation values between the two age groups. Our results revealed that there were 7CpG sites resided on 3 gene fragments showed significant difference between the adolescent group and the elderly group. It implied that some of them may be potential markers for forensic age prediction in Chinese Han population and that pyrosequencing was an effective method to screen AR-CpGs and quantify the methylation values of them.